2020
DOI: 10.1002/lary.28539
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Recognition of Laryngoscopic Images Using a Deep‐Learning Technique

Abstract: Objectives/Hypothesis: To develop a deep-learning-based computer-aided diagnosis system for distinguishing laryngeal neoplasms (benign, precancerous lesions, and cancer) and improve the clinician-based accuracy of diagnostic assessments of laryngoscopy findings. Study Design: Retrospective study. Methods: A total of 24,667 laryngoscopy images (normal, vocal nodule, polyps, leukoplakia and malignancy) were collected to develop and test a convolutional neural network (CNN)-based classifier. A comparison between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
108
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(109 citation statements)
references
References 23 publications
(37 reference statements)
0
108
0
1
Order By: Relevance
“…Recent studies confirmed the potential of FCNNs in the automatic diagnosis of benign and malignant diseases of the upper aero-digestive tract (22)(23)(24)(25)(26), demonstrating an outstanding Acc, comparable with that of experienced physicians. However, these studies were only focused on tumor detection and did not include OC and anterior OP tumors since the examination was only based on transnasal/transoral flexible video-endoscopy.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Recent studies confirmed the potential of FCNNs in the automatic diagnosis of benign and malignant diseases of the upper aero-digestive tract (22)(23)(24)(25)(26), demonstrating an outstanding Acc, comparable with that of experienced physicians. However, these studies were only focused on tumor detection and did not include OC and anterior OP tumors since the examination was only based on transnasal/transoral flexible video-endoscopy.…”
Section: Discussionmentioning
confidence: 71%
“…In fact, the operator usually centers the endoscopic image on the lesion to be identified, leading to a significant bias in automatic segmentation by FCNNs. The key role of illumination has also been emphasized by others (22,23), even showing different diagnostic performances in relation to the types of endoscopic device employed (23). In this view, novel advances in the field of image analysis should be supported by a parallel technical evolution of endoscopes, especially in terms of homogeneous illumination, high definition, colors, and optimization of image clarity.…”
Section: Discussionmentioning
confidence: 97%
“…ARDS can be developed in COVID-19 pneumonia subjects, in which a "cytokine storm" attacks endothelial cells in multiple organs, including lung alveolar epithelial cells. The "cytokine storm" attack will eventually lead to damaged blood gas exchange, inactivated pulmonary surfactant, resulting in the formation of hyaline membrane in the alveolar space, severe pulmonary edema, and disruption of lung parenchyma structure and functions (37,47). Since GLP-1-based drugs exert multiple beneficial effects in the lung, making them potential repurposed drug candidates for treating COVID-19 with or without T2D.…”
Section: Discussionmentioning
confidence: 99%
“…In einer aktuellen Studie wurden 19.000 Weißlicht-Endoskopiebilder von Stimmlippenläsionen durch ein Expertengremium aus HNO-Ärzt*innen sowie mithilfe eines Deep-Learning-Algorithmus analysiert und anschließend mit dem histopathologischen Untersuchungsergebnis (benigne Läsion vs. Leukoplakie vs. maligne Neoplasie) verglichen. Dabei schnitt das KI-System kategorieübergreifend signifikant besser ab als der Mensch (Korrektklassifikationsrate von 94 vs. 62 %) [ 25 ].…”
Section: Ki In Der Kopf-hals-onkologieunclassified